Proliferation effects of human Fetal Osteoblast cell line (hFOB 1.19) treated with Quercus Infectoria galls extract - Rozelan, Dalila (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2013)
The Quercus infectoria (QI) galls are traditionally reported to have great medicinal value such as astringent effect, anti-pyretic, anti-diabetic, anti-tremorine, anti-inflammatory, antibacterial, anti-viral and anti-oxidant activity. Those activities were postulated due to the presence of polyphenols which are proven to have an anabolic effect on the bone metabolism by modulating the proliferation, differentiation and mineralization of osteoblasts. Furthermore, Ql galls also contain mineral compositions such as calcium, phosphorus, magnesium, iron, zinc, oxygen, potassium, aluminium, carbon, manganese, nickel and silica, which are important for bone metabolism. The present study was undertaken to evaluate the effect of Ql galls extract on proliferation, bone formation markers such as alkaline phosphatase (ALP) and osteocalcin level, and morphology of hFOB 1.19 cells. The cells were cultured in Dulbecco's modified eagle medium F12 supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin, and then were treated with QI galls extract at various concentrations ranging from 0.1 to 99.0 J.lg/rnl for 72 hours. The proliferation activity of hFOB 1.19 treated with QI galls extract was measured by MIT assay with median effective concentration (EC50) 10.30 J.lg/ml. This concentration was more effective compared to positive control drug, pamidronate which exert the ECso at 16.09 J.lg/ml. In addition, the functional activity such as ALP and osteocalcin levels, were measured by enzyme-linked immunosorbent assay (ELISA) method at day 1, 3, 7, 10 and 14. The ALP activity for hFOB 1.19 treated with QI galls extract were increased in time dependent manner. The ALP highest activity in the QI galls extracts treated cells recorded as 38.79 UIL. This trend were also observed in hFOB 1.19 treated with pamidronate. However, the cells treated with QI galls extract exerted higher ALP activity compared to cells treated with pamidronate (28.03 U/L). Meanwhile, osteocalcin level for hFOB 1.19 treated with QI galls extract also were increased in time dependent manner. The highest osteocalcin level in Ql galls extract treated cells was 2.18 ng/ml. However, the osteocalcin level in hFOB 1.19 treated with pamidronate peaked at day 10 (1.54 ng/ml) and the level decreased afterward. Overall, the cells treated with QI galls extract still exerted higher osteocalcin level compared to cells treated with pamidronate. The morphology of hFOB 1.19 was observed by using inverted microscope from day I until day I4. The QI galls extract treated cells showed an increment in the cell number (percentage of raise in cell no. on day 1 = 81.48% and day 14 = 96.18%). More interestingly, cells treated with Ql galls extract remain uniformly elongated and overconfluent. Inversely, cells treated with pamidronate observed as rounded and less density (percentage of raise in cell no. on day I = 76.I9 % and day I4 = 92.19 % ). In conclusion, the result of functional activity and morphological changes of the cells were consistent and the effect of QI galls extract on proliferation of osteoblasts was much better than pamidronate. Thus, these suggest that QI galls extract might be a potent anabolic agent that able to enhance the proliferation, differentiation and mineralization of the osteoblast cells.